Efficacy of Personalized Postoperative Epilepsy Management in Patients with Glioblastoma Utilizing IDH1 Gene Assessment - Meng GQ; Chen S; Ye HB; Ma BJ; Tao S; Ye Z (Neuropsychiatric Disease and Treatment, 2024)
Gao-Qiang Meng,1,* Shu Chen,2,* Han-Bin Ye,1 Bao-Jun Ma,1 Shuo Tao,3 Zi Ye1 1Department of Neurosurgery, Affiliated Hospital 2 of Nantong University, Nantong First People’s Hospital, Nantong, 226000, People’s Republic of China; 2Department of Endocrinology, Affiliated Hospital 2 of Nantong University, Nantong First People’s Hospital, Nantong, 226000, People’s Republic of China; 3Department of Out-Patient, Affiliated Hospital 2 of Nantong University, Nantong First People’s Hospital, Nantong, 226000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zi Ye, Department of Neurosurgery, Affiliated Hospital 2 of Nantong University, Nantong First People’s Hospital, No. 666 of Shengli Road, Chongchuan District, Jiangsu, Nantong, 226000, People’s Republic of China, Email yezileafff@126.com Shuo Tao, Department of Out-patient, Affiliated Hospital 2 of Nantong University, Nantong First People’s Hospital, No. 666 of Shengli Road, Chongchuan District, Jiangsu, Nantong, 226000, People’s Republic of China, Tel +86 0513 81111429, Email xueleitaonshxzh@126.comObjective: We explored the correlation between the presence of isocitrate dehydrogenase-1 (IDH1) mutations and the incidence of postoperative epilepsy in patients with glioblastoma, as well as assessed the efficacy of preemptive administration of antiepileptic medications in mitigating the occurrence of postoperative epilepsy.Methods: Fifty-three patients who received a postoperative pathological diagnosis of glioblastoma, were enrolled in this study. Tumor specimens were subjected to IDH1 gene analysis. The patient cohort was stratified based on their IDH1 mutation status and the administration of prophylactic antiepileptic drugs during the postoperative phase. We subsequently conducted a comparative analysis of postoperative epileptic complications within each patient subgroup.Results: In the cohort of 53 patients under study, the occurrence of epilepsy was observed in 10 out of 21 patients carrying IDH1 mutations, while 5 out of 32 patients with wild-type IDH1 also experienced epilepsy, revealing a statistically significant difference (P < 0.05). Among the 27 patients who received prophylactic antiepileptic drugs, 6 of them developed epilepsy, whereas 9 out of 26 patients who did not receive prophylactic antiepileptic drugs exhibited concurrent epilepsy, with no statistically significant difference (P > 0.05). However, when performing a subgroup analysis, it was found that 3 out of 12 patients with IDH1 mutations who received prophylactic antiepileptic drugs experienced epilepsy, whereas 7 out of 9 patients who did not receive prophylactic antiepileptic drugs developed epilepsy, demonstrating a statistically significant difference (P < 0.05). Furthermore, within the group of 15 patients with wild-type IDH1, 3 patients who received prophylactic antiepileptic drugs developed epilepsy, while 2 cases of epilepsy occurred among the 17 patients who did not receive prophylactic antiepileptic drugs, with no statistically significant difference (P > 0.05).Conclusion: In individuals with IDH1 mutant glioblastoma who have undergone surgical resection, the implementation of preventive antiepileptic therapy demonstrates a potential to diminish the occurrence of postoperative epilepsy.Keywords: epilepsy, glioblastoma, isocitrate dehydrogenase-1, prophylactic antiepileptic therapy